Zróżnicowanie wyznaniowe stylu religijnego. Analiza na podstawie polskich modlitw ewangelickich, katolickich i prawosławnych - Pawlikowska, Aleksandra (Stylistyka, 2019)
The paper is about confessional differences in Polish religious style. In Polish linguistics there is interest in religious communication, but most of the research applies only to Catholic texts. Besides Catholicism, there are many various Christian and non-Christian religious communities which should be analyzed. The basis for the analysis were prayers of Polish Catholicism, Lutheranism and Orthodoxy. These are three biggest religious communities in Poland. Very important were he structural, pragmatic and cognitive aspects of texts. The method of the analysis was statistics. The statistical analysis showed that there are a lot of differences, especially in the lexis and pragmatics of prayers, like creation of God and man, speech acts, entropy and redundancy, lexical fields, etc. All of these are determined by theological and ideological rules of the confessions. But it is important to remember that all the texts are still a realization of one style.